2017
DOI: 10.1038/sj.bdj.2017.765
|View full text |Cite
|
Sign up to set email alerts
|

Social media and professionalism: a retrospective content analysis of Fitness to Practise cases heard by the GDC concerning social media complaints

Abstract: Neville, P. (2017). Social media and professionalism: a retrospective content analysis of Fitness to Practice cases heard by the GDC concerning social media complaints. British Dental Journal, 223 (5) University of Bristol -Explore Bristol Research General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms Method: Documentary analysis of soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…If this situation is not resolved, then students will begin to appear in the GDC's Fitness to practice cases. 21 More research will need to be undertaken to explore how we can inculcate eprofessional norms, values and behaviours so we can prepare the 21st century dentist. For all these reasons, it is important that social media becomes a mainstream element of the education of healthcare students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If this situation is not resolved, then students will begin to appear in the GDC's Fitness to practice cases. 21 More research will need to be undertaken to explore how we can inculcate eprofessional norms, values and behaviours so we can prepare the 21st century dentist. For all these reasons, it is important that social media becomes a mainstream element of the education of healthcare students.…”
Section: Discussionmentioning
confidence: 99%
“…13 14 In fact, there is an ongoing debate within the BDJ on the impact and significance of social media on dentistry and dental professionalism. [15][16][17][18][19][20][21] While a lot of research has been conducted on the online behaviours of medical and allied health professional students (see above), less has been undertaken on dental students, except for Kenny and Johnson 22 and Nason et al 23 Mindful of this gap in our knowledge, this research was conducted to explore the social media habits of dental students and their views on e-professionalism. Its aim was to determine whether students were aware of the standards set by the GDC regarding social media and whether they believed they were being professional in their online activities.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that healthcare students have used Facebook to breach patient confidentiality in various postings (Thompson 2010), engage in online relationships with patients (Nyangeni, du Rand, and van Rooyen 2015), and write disrespectful comments about colleagues and employers (Chretien, Greysen, Chretien, and Kind 2009;Hall, Hanna, and Huey 2013). Neville (2017b) found that most of the Fitness to Practise cases investigated and upheld by the General Dental Council over a three-year period in the UK involved Facebook posts. As a result, Facebook, as a participatory social networking site, provides an opportunity to explore how the norms, values, and behaviours of professionalism are interpreted and constructed by today's young healthcare professionals.…”
Section: Facebook Cyber Vawg and Misogynymentioning
confidence: 99%
“…11 In addition, there have been disciplinary actions due to social media use. 12 Two dental nurses were reprimanded due to comments posted on encountered by dentists and DCPs when using social media and the approaches used to manage these conflicting demands. To address the aim the two questions considered were:…”
Section: Introductionmentioning
confidence: 99%